Pengaruh Keterlibatan Mahasiswa dalam Organisasi terhadap Tingkat Self-Confidence di Lingkungan Perguruan Tinggi - Prameswari, Marsha Ayudhya; Al Islam, Iyuz; Ardianti, Anandita; Putri, Verisca Meyliana; Safitri, Salsabila Rifa; Nugraha, Joko Tri (FIA Unkris Press, 2026)
This study aims to analyze the effect of student involvement in organizations on self-confidence levels, using a quantitative approach with a causal survey design. The background of this research is based on the importance of developing students' character and potential not only through academic learning but also through real-life experiences in organizational environments, which serve as social laboratories for developing mature personalities. The study sample consisted of 100 students, determined using the Slovin formula with a 10% margin of error. They were selected through simple random sampling. The instrument was a Likert-scale questionnaire with proven validity and very high reliability (Cronbach's Alpha = 0.933). Data collection was carried out by distributing questionnaires directly, then analyzed using correlation tests and simple linear regression to determine the direction, strength of the relationship, and the magnitude of the influence between the variables. The analysis results showed a very strong positive relationship between the two variables (r = 0.732) and a significant effect with a contribution of 54%, formulated in the regression equation Y^=5.18+0.60X. This figure indicates that organizational involvement has a significant impact on building self-confidence, while the remaining variables are influenced by factors outside of this study. These results conclude that the more active and intense a student's involvement in an organization, the higher their self-confidence. This confirms that student organizations play a crucial role as a means of student self-development outside of classroom learning. Therefore, their existence needs to be optimized by educational institutions to produce graduates who are not only academically intelligent but also possess strong self-confidence and social skills.